Expression of hypoxia inducible factor-1α (HIF-1α) gene and apoptosis in the heart induced by systemic hypoxia (Medical Journal of Indonesia, 2009)
Aim This study explored the expression of HIF-1α in hypoxic cardiac muscle in mice, and observed the evidence of apoptosis in hypoxia induced cardiomyocyte. Methods Male Sprague-Dawley rats, were randomized into 7 groups (n = 4 per group): control normoxia group that was exposed to atmospheric oxygen and hypoxia groups that were housed in hypoxic chambers (O2 level 8%) for 1, 3, 7, 14, 21, and 28 days respectively. Animals were sacrificed, hearts were rapidly excised, total RNA was extracted with an mRNA isolation kit and the expression of HIF-1Î± mRNA was then detected by real-time RT-PCR. Apoptosis was assessed by TUNEL method. Results For rat in hypoxia group, the expression of HIF-1α mRNA in cardiac myocytes was clearly up-regulated compared to the control normoxia group. Further, HIF-1α expression level elevated gradually and reached a peak at 21 days of hypoxia. No cell labeled by the TUNEL method was detected in the control group. Compared with the control group, the apoptotic index was significantly increased in the hypoxia group (P < 0.05). There was no significant correlation between the elevation of HIF-1α mRNA and the elevation of apoptotic index. Conclusion Systemic chronic hypoxia caused the elevation of HIF-1α mRNA and apoptosis in cardiac myocytes. (Med J Indones 2009; 18: 97-101) Keywords: TUNEL, RT-PCR, mRNA, apoptotic index